1987
DOI: 10.1016/0035-9203(87)90372-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and population dynamics of Ascaris lumbricoides and Trichuris trichiura infection in the same community

Abstract: The gastrointestinal helminth infection status of an age-stratified sample from a single Caribbean community was assessed using anthelmintic expulsion techniques. The same sample was re-assessed in a similar manner after a 17 month period of re-infection. The age-prevalence profile of Ascaris lumbricoides was convex while that of Trichuris trichiura was asymptotic. The age-intensity profiles of both species were convex. These differing patterns are attributed to differences in the absolute worm burdens of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 19 publications
5
42
1
Order By: Relevance
“…Children aged 2 to 12 years more frequently had infections of greater intensity than individuals older than 12. Surveys completed in communities in other countries have shown that the prevalence of Ascaris drops in people older than 15 years (Bundy et al 1987, Reinthaler et al 1988, Hasegawa et al 1992, Upatham et al1992, Mangali et al 1994. However, the prevalence of Trichuris does not drop off in adulthood (Bundy et al 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children aged 2 to 12 years more frequently had infections of greater intensity than individuals older than 12. Surveys completed in communities in other countries have shown that the prevalence of Ascaris drops in people older than 15 years (Bundy et al 1987, Reinthaler et al 1988, Hasegawa et al 1992, Upatham et al1992, Mangali et al 1994. However, the prevalence of Trichuris does not drop off in adulthood (Bundy et al 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The association between the number of children aged 2-5 years or 6-14 years living in the household and parasite infection may have occurred because children less than 15 years old constitute the age group that is most frequently infected by Ascaris and Trichuris (Bundy et al 1987, Reinthaler et al 1988, Hasegawa et al 1992, Upatham et al 1992, Mangali et al 1994. The association of A. lumbricoides with diarrhea could be due to general uncleanliness within the household, or other confounders not controlled for, since (Genta 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Age-intensity relationships similar to that found in our study were reported in Nigeria, where hookworm intensity peaked in the 15-19 age group then declined rapidly (Udonski 1980), and in females of West Bengal, India (Schad et al 1975). Such an age-intensity pattern is more commonly seen in other nematode infections such as Trichuris trichura and A. lumbricoides (Bundy et al 1987), but is rare in the case of hookworm. Differences in the age-intensity patterns of hookworm may be due to differences in the relative abundance of N. americanus and A. duodenale, perhaps because of differences in transmission dynamics of mixed infections (Behnke 1987).…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological parameters used in the model are given in Table 1. Population size was assumed to be 100 000, of whom CROLL et al (1982) for the high transmission area and CHAI et al (1985) and BUNDY et al (1987) for the low transmission area. The parameter k, an index of the degree of parasite aggregation, was taken from GUYATT et al (1990) and the disease threshold (T) was based on analysis by GLJYATT & BUNDY (1991).…”
Section: Base Casementioning
confidence: 99%